Ammonia-treated porous carbon derived from ZIF-8 for enhanced CO2 adsorption - Ma, X.; Li, L.; Wang, Shaobin; Lu, M.; Li, H.; Ma, W.; Keener, T. (Elsevier BV North-Holland, 2016)
A porous carbon (ZC) was prepared at 900 °C using zeolitic imidazolate framework-8 (ZIF-8) as a solid template for CO2 adsorption. The ZC was further treated by ammonia functionalization to improve CO2 uptake. The textural and surface characteristics of ZC samples were determined by X-ray diffraction (XRD), N2 adsorption, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). It was revealed that ammonia treatment at 600 °C considerably enhanced the specific surface area and N-content of ZC. However, the pyrrolic-N group was decreased, yet the pyridinic-N group was increased with an increased temperature. The pyrrolic-N significantly enhanced CO2 adsorption. The ammonia treatment, on the one hand, increases the alkalinity of ZC sample and the base–acid interaction between N-containing functional groups with CO2. On the other hand, the ammonia treatment increased pyrrolic-N group (NH) into carbon surface facilitating the hydrogen-bonding interactions between proton of pyrrolic-N and CO2 molecules.